Femoral nerve palsy during Pavlik harness treatment for developmental dysplasia of the hip is not an indication for harness abandonment. (June 2023) - Ghanem, Ismat; Karam, Geoffrey; Ghanem, Diane; Saliba, Ibrahim
Objectives: The aim of this study was to report the incidence of femoral nerve palsy in developmental dysplasia of the hip children treated with Pavlik harness, to identify any possible associated risk factors, and to evaluate its outcome without any specific strap release. Methods: A retrospective chart review was conducted on all cases of femoral nerve palsy in a consecutive series of children who underwent Pavlik harness treatment for developmental dysplasia of the hip. In unilateral cases, the developmental dysplasia of the hip was compared to the contralateral side. All hips with femoral nerve palsy were compared to the remaining hips of the series and any possible risk factor for paralysis was recorded. Results: In total, 53 cases of femoral nerve palsy of various severity were identified from a group of 473 children with 527 hips treated for developmental dysplasia of the hip at an average age of 3.9 months. However, 93% occurred during the first 2 weeks of treatment. Femoral nerve palsy was more common in older and larger children with the most severe Tonnis type, and a hip flexion angle in the harness above 90° (p < 0.03 for all). All of them resolved spontaneously before completion of treatment without any specific measures. We found no correlation between the presence of femoral nerve palsy or the time taken for spontaneous resolution and treatment failure using the harness. Conclusion: Femoral nerve palsy is most observed with higher Tonnis types and high hip flexion angles in the harness, but its presence by itself is not predictive of treatment failure. It resolves spontaneously before completion of treatment and does not require any strap release or harness discontinuation. Level of evidence: Level III.